Long-term alteration of heart rate variability following childhood maltreatment: Results of a general population study - Marian Stürmer; Johanna Klinger-König; Marcus Vollmer; Antoine Weihs; Stefan Frenzel; Marcus Dörr; Lars Kaderali; Stephan B. Felix; Beate Stubbe; Ralf Ewert; Henry Völzke; Hans J. Grabe; et al. (European Psychiatry, 2025)
Abstract Background Childhood maltreatment (CM) is a risk factor for mental and physical health problems in adulthood, potentially mediated by long-term autonomic nervous system (ANS) dysregulation. To explore this link, the association between CM and vagal-sensitive heart rate variability (HRV) metrics in adults was examined, accounting for biopsychosocial factors.